The Effect of Probiotic Therapy on the Vagina Microbiota and the Humoral Link of Immunity in Bacterial Vaginosis - Mykhailyshyn, H.I.; Klumnyuk, S.I.; Spivak, M.Ya.; Sverstiuk, A.S.; Lazarenko, L.M.; Михайлишин, Г. І.; Климнюк, С.І.; Співак, М.Я.; Сверстюк, А.С.; Лазаренко, Л.М. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The aim of the research is to determine the effect of the probiotic preparation «Dialak» (dietary supplement), which includes the strain Lactobacillus casei IMV B-7280, on the vaginal microbiota and humoral immunity in women with bacterial vaginosis (BV). Methods. 40 female patients aged 20—45 years with disturbed vaginal microbiota and 10 healthy individuals were examined. The verification of 3 types of vaginal biocenosis states, namely normocenosis, intermediate type, and vaginal dysbiosis, was carried out on the basis of the Recommendations for the Treatment of Sexually Transmitted Infections Weekly Morbidity and Mortality Report (2021) and laboratory diagnostic methods according to the well-known criteria proposed by R. Amsel. Female patients with an intermediate type of BV (group 1) received suppositories and capsules of the probiotic (once daily) for 10 days. Women with vaginal dysbiosis (group 2) received metronidazole in a dosage of 500 mg twice a day for 7 days during the first stage, and then 1 suppository at night and oral capsules of the probiotic in the morning for 10 days during the second stage. The studied vaginal secretion was stained by the Gram method in the Kopeloff modification and also sown on nutrient media to determine facultatively anaerobic and obligately anaerobic microorganisms. Microorganism identification was carried out on the basis of morphological, cultural, biochemical, and antigenic properties according to the classification of D. H. Bergey (2009). The activity of humoral immunity was determined by evaluating the number of B-lymphocytes in the peripheral blood of patients using flow cytometry, as well as the levels of serum Ig A, M, and G before treatment and aft er 1 month using the immunoturbidimetric method and the Cobas 6000 test system from Roche Diagnostics (Switzerland). Results. When analyzing the vaginal microbiota in two groups of patients before treatment, a decrease in the number of Lactobacillus spp. and Bifidobacterium spp. and a significant increase in the number of obligate anaerobic microorganisms, including Gardnerella vaginalis, were found compared to the control group. Before treatment, the number of Lactobacillus spp. in women of group 2 was lower compared to group 1. In patients with vaginal dysbiosis before treatment, the number of obligate anaerobic microorganisms was higher than in patients with bacterial vaginosis, except for Eubacterium spp. At the same time, in women in both comparison groups, the indicators of the humoral immune response were partially disrupted, as evidenced by a decrease in the level of IgG and IgA (in women of group 2) in the serum against the normal level of B lymphocytes (CD19+ cells). However, these patients showed an increase in the IgM level in the serum, which may be due to the development of anaerobic microflora. After treatment, the number of Lactobacillus spp. and Bifidobacterium spp. in the vagina of women in both comparison groups increased compared to the indicators before treatment. However, the number of these bacteria in the vagina of patients with dysbiosis remained lower compared to patients with BV. In both groups, normalization of the number of obligate anaerobic microorganisms, including G. vaginalis, except for Veillonella spp., was also observed. After treatment, the humoral immune response indicators were normalized as well: the level of serum IgG and IgA increased, and the content of serum IgM decreased. Conclusions. In BV patients, the probiotic «Dialak» normalizes the vaginal microbiota, which was confirmed by increasing the number of Lactobacillus spp. and Bifidobacterium spp. along with decreasing the number of anaerobic microorganisms, including G. vaginalis, against the background of the dynamic disappearance of clinical signs of the disease, as well as restoration to the normal level of indicators of the immunity humoral link. The obtained data indicate the effective therapeutic effect of the probiotic «Dialak» on BV.